PENGARUH LATIHAN PRESSURE SHOTS TERHADAP HASIL SHOOTING SEPAKBOLA CLUB AS ABADI PEKANBARU - Sardotua Alhamid Pane; Zainur Zainur; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstact: The problem in this research is that they don't maximize the chances of scoring goals against the opponent's goal when they are under pressure from the opposing team, the aim of this study is to improve the marksmanship of athletes to decide. The format of this research is (one group pretest-posttest design) with the population of SSB Club AS Abdi Pekanbaru. The data in this research was the entire population of 16 subjects. The instrument used in this research was the use of a shooting test. Based on the analysis of the normality test on the independent variable (X), it produces LoMax of 0.168 and Ltable of 0.213, meaning LoMax < Ltable. while the dependent variable (Y) produces LoMax of 0.191 and Ltable of 0.213. This means that LoMax < L The data table is normally distributed. When testing the t distribution hypothesis, it can be concluded that between the x variable and y variable, the value t = 7.756, then tcount > ttable that is (7.756) > (1.753), then Ha is accepted, in other words there is an effect of practicing pressure shots on the results of shooting American club football.Eternal Pekanbaru.Key Words: Practice Pressure Shots, Shooting, Football